The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/jam.15708
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of inhibitory compounds produced by bacteria isolated from a hydrogen-producing bioreactor during the self-fermentation of wheat straw

Abstract: Aims:The objective of this study was to evaluate the inhibitory activity of compounds secreted by bacteria isolated from a hydrogen-producing bioreactor to understand how these microorganisms interact in this community. Methods and Results:In vitro inhibitory assays were performed using samples secreted by bacteria subject to different treatments to determine if their inhibitory effect was due to organic acids, non-proteinaceous compounds or bacteriocin-like inhibitory substances (BLIS). Bacterial isolated wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…On the other hand, the lactic acid bacterium Lactobacillus has also been reported in hydrogen-producing reactors via CBP (Ayala-Campos et al 2022 ; Pérez-Rangel et al 2023 ). These two LAB seem to establish different interactions with hydrogen producers; for example, Pérez-Rangel et al ( 2022 ) reported antagonism between Lactobacillus – Enterococcus and Enterococcus – Clostridium , but not between Lactobacillus – Clostridium . Notably, in those processes where Lactobacillus and Clostridium thieved together, there was no accumulation of lactic acid, which strongly suggests the occurrence of the lactic acid-based pathway.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the lactic acid bacterium Lactobacillus has also been reported in hydrogen-producing reactors via CBP (Ayala-Campos et al 2022 ; Pérez-Rangel et al 2023 ). These two LAB seem to establish different interactions with hydrogen producers; for example, Pérez-Rangel et al ( 2022 ) reported antagonism between Lactobacillus – Enterococcus and Enterococcus – Clostridium , but not between Lactobacillus – Clostridium . Notably, in those processes where Lactobacillus and Clostridium thieved together, there was no accumulation of lactic acid, which strongly suggests the occurrence of the lactic acid-based pathway.…”
Section: Introductionmentioning
confidence: 99%